PENGARUH FAKTOR PRESPEKTIF BWI-SU TERHADAP PELUANG PENINGKATAN DANA WAKAF PRODUKTIF DI SUMATERA UTARA - Syahbudi, muhammad; Alwainiy, Irfah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2015)
BWI-SU existence in waqf plays a very important for developing or not all waqf property. Nazhir assigned the duty to maintain and administer endowments objects, where this sense then in Indonesia developed into a group of persons or legal entities entrusted with the task to maintain and take care of charitable objects. In addition, Nazhir also have an obligation to maintain, develop and preserve the benefits from property for people who are entitled to get it, means that the function and malfunction of an waqfÂ depending on Nazhir. This paper aims to determine the effect of the variable perspective of Nazhir namely managers in BWI SU against the odds increase endowment fund. The authors conducted a survey on the BWI SU. Sampling method used is convenience sampling method on 20 Nazhir or managers of waqf. Writer using multiple regression method. In this study the variable perspective endowment managers at BWI SU consists of professionalism, socialize, network and data base where these variables is the source of the increase in endowment funds. So the goal of the author that in order to maintain the professionalism, continue to socialize and build a network line and further increase in the application database.